‘As We May Digitize’ — Institutions and Documents Reconfigured - Dahlström, Mats; Hansson, Joacim; Kjellman, Ulrika (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
This article frames digitization as a knowledge organization practice in libraries and museums. The primarily discriminatory practices of museums are compared with the non-discriminatory practices of libraries when managing their respective cultural heritage collections. Digitization of cultural heritage brings new practices, tools and arenas that reconfigure and reinterpret not only the collections, but the memory institutions themselves as well as the roles they respectively play on a societal level. The development of digitization promises to bridge some gaps between libraries and museums, either by redefining their respective identity, or by forming new ground where the interests of the respective institutions naturally meet or even converge, or by neglecting particular tasks and roles that do not seem to find a natural home in the new territory. Two poles along a digitization strategy scale, mass digitization and critical digitization, are distinguished in the article. As memory institutions are redefined in their development of digitized document collections, e.g., by increasingly emphasizing a common trans-national rather than national cultural heritage, mass digitization and critical digitization represent alternative avenues. Museums, libraries and archives (MLA) endeavour aiming for joint tools and practices in digitizing cultural heritage collections need a thorough understanding of such mechanisms. The article re-contextualizes current digitization discourse: a) historically, by suggesting that digitization brings ancient practices back to life rather than invents entirely new ones from scratch; b) conceptually, by presenting a new label (critical digitization) for a digitization strategy that has hitherto been downplayed in digitization discourse; and c) theoretically, by exploring the relations between the values of different digitization strategies, the reconfiguration of collections as they are digitized, and the redefinition of MLA institutions through those processes. The arguments in the article are drawn from examples of digitization in different library contexts on both a national (Swedish) level and a European level.